Molecular Imprinted Polymers for Macrolides, Aminoglycosides and Some Other Biosynthetic Antibiotics - M. I. Yakhkind; K. R. Tarantseva; M. A. Marynova; P. A. Storozhenko; M. M. Rasulov (Антибиотики и Химиотерапия)
Molecular imprinted polymers (MIP) for macrolides, aminoglycosides and some other biosynthetic antibiotics described in the literature were analysed with a purpose of evaluating their possible use for the antibiotics sorption.